Phytochemical constituent scening of Azinza garckena roots with claimed effect on induction of labour in Monze West-Zambia - Kaonga Wezi (Lusaka, the university of Zambia, school of medicine, 2016)
The phytochemical of herbs used by pregnant women and traditional birth attendants for the induction of labour is an important step in validating the perceived use, physiological effect and leads to the discovery and isolation of novel compounds that are of medicinal values. Azanza garckeana root extract is used for labour induction by traditional birth attendants in Monze west Zambia.
A dissertation submitted in partial fulfilment for the award of pharmacy degree at the university of Zambia.
Keywords: Labour induction; pregnancy